Industrial Policy in the African Context - Stiglitz, Joseph (World Bank, Washington, DC, 2014)
After long suffering from benign neglect if not outright contempt, industrial policy is almost fashionable again. The global financial and economic crisis known as the Great Recession has forced researchers and policy makers to confront the reality that market forces alone generally do not lead to (constrained) Pareto-efficient outcomes. Many important national and global policy objectives (equality of opportunity for all citizens, financial stability and inclusion, environmental protection and pollution control, etc.) are simply often not reflected in market prices and not achieved by markets on their own. In addition to traditional justification for industrial policies -- dealing with externalities and coordination issues economists and policy makers now acknowledge the need to foster learning at the level of each economic agent and throughout society and the ultimate responsibility that the state must bear in that crucial process. But converting the now widely accepted theoretical principles of industrial policy into practical frameworks for concrete government action is indeed a daunting task everywhere and perhaps more so in the African context where the institutional underpinnings of effective government are often not as strong as one might have hoped. This essay highlights the intellectual foundations and broad principles of good industrial policy, outlines the contours of the policy agenda, and fleshes out the lessons learned. It argues that there has been substantial progress on the understanding and acceptance of industrial policy and that Africa could benefit enormously from it and from the unprecedented new opportunities brought to light by a multipolar world.